SNIFFING AROUND FOR CLINICAL SCREENING MARKERS TO PREDICT AERD IN CRSWNP PATIENTS - Coyle, T.; Fishbein, J.; Tham, T.; Shapero, M.; Fastenberg, J.; Bruni, M.; Kaplan, B. (Annals of allergy, asthma, & immunology, 2022)
Aspirin-exacerbated respiratory disease(AERD) is a sub-group of chronic rhinosinusitis with nasal polyps(CRSwNP) associated with asthma and cyclooxygenase-1 inhibitor sensitivity. AERD pathogenesis involves dysregulation of arachidonic acid metabolism which favors pro-inflammatory mediator overproduction. A significant proportion of AERD patients are suspected to be undiagnosed, as aspirin sensitivity is frequently unreported. There are no standard AERD screening modalities but aspirin challenge(AC) is an effective diagnostic tool. A retrospective, observational study was conducted from 1/1/2016-12/29/2021. 210 subjects met inclusion criteria of CRSwNP patients who underwent AC, desensitization or had clinically diagnosed AERD. Baseline level of serum eosinophils(EOS), basophils, immunoglobulins, complements, tryptase, spot urine leukotriene E4(LTE4), fractional exhaled nitric oxide(FeNO) and Lund-Mackay CT-sinus score(LMCT) were evaluated. 33 subjects on biologic therapy were excluded. AERD was diagnosed in 74/177(41.80%) subjects. 61 subjects denied NSAID sensitivity and then completed AC, from which 14/61(22.95%) were positive. Several markers showed significant correlation with positive AC including LMCT, EOS and LTE4. Total complement(CH50) showed a slight but significant negative trend with positive AC but values remained within normal range. Other markers showed no correlation. Contemporary literature reports different AERD endotypes which may obscure clinical phenotypes and hamper diagnosis. Clinical markers could prove valuable screening tools for atypical phenotypes. Prior studies have correlated AERD with serum basophils, EOS, IgE, LTE4 and LMCT. Our data correlates AERD diagnosis with LMCT, EOS, LTE4 and CH50. Further studies are needed to confirm our CH50 results. These clinical, laboratory and radiologic markers could prove useful screening tools for identifying candidates for AC.